Nano-revolution in heavy metal removal: engineered nanomaterials for cleaner water - Karnwal, Arun; Malik, Tabarak (Frontiers in Environmental Science, 2024)
Engineered nanomaterials have emerged as a promising technology for water treatment, particularly for removing heavy metals. Their unique physicochemical properties enable them to adsorb large quantities of metals even at low concentrations. This review explores the efficacy of various nanomaterials, including zeolites, polymers, chitosan, metal oxides, and metals, in removing heavy metals from water under different conditions. Functionalization of nanomaterials is a strategy to enhance their separation, stability, and adsorption capacity.Experimental parameters such as pH, adsorbent dosage, temperature, contact time, and ionic strength significantly influence the adsorption process.In comparison, engineered nanomaterials show promise for heavy metal remediation, but several challenges exist, including aggregation, stability, mechanical strength, long-term performance, and scalability. Furthermore, the potential environmental and health impacts of nanomaterials require careful consideration. Future research should focus on addressing these challenges and developing sustainable nanomaterial-based remediation strategies. This will involve interdisciplinary collaboration, adherence to green chemistry principles, and comprehensive risk assessments to ensure the safe and effective deployment of nanomaterials in heavy metal remediation at both lab and large-scale levels.